PENERAPAN GENIUS LOCI PADA PEMUKIMAN MASYARAKAT NGADAS TENGGER MALANG - Hammam Rofiqi Agustapraja (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Settlement is a human living environment that has distinctive characteristics and serves as a place,  space,  and  container  for  the  growth  and  development  of  human  culture  as  part  of  the residential  community.  If  in  a  permukinman  community  has  undergone  changes,  growth  and development, it will certainly have an impact on the human being that is part of the community. The elements of settlement include the spatial pattern formed on the micro scale to the macro scale (village) is strongly influenced socio-cultural factors of society.